Ethanol Extract of Bajakah Wood (Spatholobus littoralis Hassk.) on Tyrosinase Concentration and Body Weight in Rats Induced with High-Dose D-galactose - Putuh Anisa, Puput; Arika, Luh Ade Lela; Harliansyah, Harliansyah; Sobarna, Nenden Lilis (Sarana Ilmu Indonesia (Salnesia), 2025)
The aging process is associated with the accumulation of oxidative stress that damages cellular function. D-galactose is used to induce aging-like conditions in animal models. Bajakah wood extract (Spatholobus littoralis Hassk.), which is traditionally used, is known to contain bioactive compounds with antioxidant activity. This study aimed to elucidate the effects of ethanol extract from Bajakah wood (Spatholobus littoralis Hassk.) on tyrosinase concentration and body weight in rats subjected to high-dose D-galactose induction. This laboratory experimental study used 36 male Sprague Dawley rats induced with D-galactose (500 mg/kgBW). The rats were divided into six groups: normal control, negative control, positive control (vitamin C 50 mg/kgBW), and three treatment groups that received Bajakah ethanol extract at doses of 25, 50, and 100 mg/kgBW. Body weight was monitored weekly for 8 weeks, and tyrosinase levels were analyzed at the end of the study. The negative control group showed fluctuations in body weight and the highest tyrosinase levels. Administration of Bajakah extract, particularly at a dose of 100 mg/kgBW, significantly reduced tyrosinase concentrations (p-value < 0,05) and resulted in a more stable weight gain profile compared to the negative control group. Bajakah wood ethanol extract showed an inhibitory effect on tyrosinase and improved weight stability in the D-galactose-induced rat model. These findings support the potential of this extract as a plant-based therapeutic agent for disorders related to oxidative stress and aging.